The effect of a short‐term Balint group on the communication ability and self‐efficacy of pre‐examination and triage nurses during COVID‐19. Issue 1 (19th November 2020) - Yang, Chenghui; Zhou, Bo; Wang, Jinyu; Pan, Shuya
Abstract: Aims and objectives: To investigate the effect of a short‐term Balint group on the improvement in communication ability and self‐efficacy of pre‐examination and triage nurses during coronavirus disease 2019 (COVID‐19). Background: Working on the front lines of COVID‐19 has brought unprecedented psychological stress on pre‐examination and triage nurses. Nurse–patient communication ability and the level of self‐efficacy are both significant for nurses' psychosomatic health and work input. However, limited empirical evidence exists regarding nurse–patient communication and self‐efficacy and specific psychological intervention effects. Design: Cross‐sectional research fulfilling the completed checklist of items that should be included in reports of cross‐sectional studies (Appendix S1). Methods: Nurses ( n  = 41) in the first layer of pre‐examination and triage were engaged in a Balint group activity twice a week for two weeks. They were assessed with the General Self‐Efficacy Scale (GSES) pre‐ and postintervention, and a nurse–patient communication survey form was developed for further postintervention evaluation. The sample was recruited from a class A third‐grade hospital in Sichuan, China. Results: Most of the subjects reported improvement in nurse–patient communication, increased cooperation between patients and their families, and a decreased missed examination rate after the intervention. Moreover, the total mean score of the GSES of nurses after the intervention was increased, but the difference was not statistically significant. The scores of all items in the GSES were improved, and the scores increase for item 4 (I am confident that I can effectively deal with any unexpected event) was statistically significant. Conclusions: During the COVID‐19 pandemic, a short‐term Balint group activity can improve the communication ability and self‐efficacy level of front‐line nurses to some extent. Relevance to clinical practice: This information may provide some theoretical support for the development of early psychological interventions during major epidemic situations.